Channel regulation through solvents for Cd‐MOFs based on p‐methoxyphenyl imidazole dicarboxylate: Synthesis, crystal structure, fluorescence, and explosive identification. Issue 2 (29th November 2021) - Jiang, Yuxuan; Dong, Jianping; Li, Ruixue; Sun, Fugang; Wu, Huilu
Abstract: Under different solvent systems, the reaction of Cd(NO3 )2 ·4H2 O with 2‐ p ‐methoxyphenyl‐1 H ‐imidazole‐4, 5‐dicarboxylic acid ( p ‐H3 MOPhIDC) ligand produce two new Cd‐MOFs, [Cd( p ‐HMOPhIDC)(C2 H5 OH)] n (1 ) and [Cd2 ( p ‐HMOPhIDC)2 (Py)(C2 H5 OH)] n (2 ). Structural analysis shows that although the two Cd‐MOFs have the same six‐coordinated distorted octahedron geometry of the Cd(II) centers and the similar framework structure, they have different coordinated polymerization unit symmetry and internal environment in the channels. Among them, the polymerization unit in the channel of Cd‐MOFs 1 is centrosymmetric, while the polymerization unit in the channel of Cd‐MOFs 2 is asymmetric. Compared with the free p ‐H3 MOPhIDC ligand, the fluorescence peaks of the two Cd‐MOFs in the solid‐state have undergone a slightly red shift and enhancement. This is due to the increased rigidity of the ligand after the coordination of the metal ions with the ligand, which reduces the energy loss of thermal vibration. The fluorescence enhancement of Cd‐MOFs 1 is greater than that of 2, which is related to the symmetry of the coordination polymerization units in the two Cd‐MOFs channels. In addition, Cd‐MOFs 2 can highly sensitive sense 2, 4‐dinitrotoluen (DNP) and 2, 4, 6‐trinitrophenol (TNP) through luminescence quenching effect, whereas 1 cannot. This result is due to the difference in the environment within their channels. Abstract : Under different solvent systems, two novel cadmium(II) organic frameworks (Cd‐MOFs), [Cd( p ‐HMOPhIDC)(C2 H5 OH)] n and [Cd2 ( p ‐HMOPhIDC)2 (Py)(C2 H5 OH)] n were synthesized. Structural analysis shows that although the two Cd‐MOFs have the same six‐coordinated distorted octahedron geometry of the Cd(II) centers and the similar framework structure, they have different coordinated polymerization unit symmetry and internal environment in the channels. The fluorescence enhancement of Cd‐MOFs 1 is greater than that of 2, which is related to the symmetry of the coordination polymerization units in the two Cd‐MOFs channels. In addition, Cd‐MOFs 2 can highly sensitive sense 2, 4‐dinitrotoluen (DNP) and 2, 4, 6‐trinitrophenol (TNP) through luminescence quenching effect, whereas 1 cannot. This result is due to the difference in the environment within their channels.